Biological Effects of Combined Inactivation of Plasminogen Activator and Plasminogen Activator Inhibitor-1 Gene Function in Mice - Lijnen, H Roger; Moons, Lieve; Beelen, Veerle; Carmeliet, Peter; Collen, Désiré (Thrombosis and Haemostasis, 1995)
Mice with combined homozygous deficiency of tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (u-PA) (T‾U‾), of t-PA and plasminogen activator inhibitor-1 (PAI-1) (T‾P‾), of u-PA and PAI-1 (U‾P‾) or of t-PA, u-PA, and PAI-1 (T‾U‾P‾) were generated by inbreeding of mice with the respective deficiencies. Homologous recombination at the t-PA, u-PA and PAI-1 locus was verified by Southern blot analysis of genomic tail tip DNA, and confirmed by measurement of antigen levels in plasma or urine.T‾P‾ and U‾P‾ mice were apparently healthy and fertile. T‾U‾ mice showed extensive fibrin deposition with calcification in the liver, whereas T‾U‾P‾ mice were significantly (p <0.001) less affected. Spontaneous in vivo clot lysis measured 4 h after injection of a 125I-fibrin-labeled clot prepared from plasma of wild-type (WT) mice into the jugular vein, was (mean ± SEM of n experiments) 2 ± 1% (n = 8) for T P , 49 ± 6% (n = 9) for U‾P‾, 1 ± 1% (n = 4) for T‾U‾ and 3 ± 3% (n = 3) for TU‾P‾ mice, as compared to 32 ± 4% (n = 10) for WT, 1 ± 0% (n = 7) for T‾, 30 ± 5% (n = 5) for U‾ and 58 ± 10% (n = 6) for P‾ mice. Plasminogen-dependent lysis of 125I-fibrin-labeled matrix and of 3H-proline-labeled subendothelial matrix (mean ± SEM; n = 4 to 6) was lower with thioglycollate-stimulated macrophages obtained from U‾P‾ mice (22 ± 7% and 5 ± 1%, respectively), as compared to WT mice (57 ± 14% and 18 ± 5%, respectively) and T‾P‾ mice (87 ± 6% and 27 ± 4%, respectively). A similar decrease was previously observed with U‾ mice, but not with T‾ or P‾ mice. Thus, the phenotype of mice with combined deficiency of t-PA and PAI-1 or of u-PA and PAI-1 is similar to the phenotype observed in mice with single deficiency of the plasminogen activator. Additional deletion of PAI-1 does not affect viability, fertility, macrophage function or thrombolytic potential of the single deficient mice. Additional deletion of PAI in mice with combined deficiency of t-PA and u-PA does not restore the deficient in vivo fibrinolytic capacity, but significantly reduces the thrombotic phenotype, as revealed by fewer, smaller and less calcified fibrin deposits in the liver.